Synergistic multi-joint kinematic strategies to reduce tripping risks during obstacle-crossing in older long-term Tai-Chi Chuan practitioners - Huang, Hsing-Po; Kuo, Chien-Chung; Lu, Shiuan-Huei; Chen, Sheng-Chang; Ho, Tsung-Jung; Lu, Tung-Wu (Frontiers in Aging Neuroscience, 2022)
Introduction Losing balance or tripping over obstacles is considered one of the most common causes of falls in the elderly. Tai-Chi Chuan (TCC) has been shown to improve muscle strength, inter-joint coordination and balance control in the elderly. This study aimed to determine whether older long-term TCC practitioners would show multi-joint kinematic strategies that would reduce the risk of tripping during obstacle-crossing compared to peers without TCC experience. Methods Three-dimensional motions of the pelvis and lower extremities were measured using a motion capture system in fifteen older long-term TCC practitioners (TCC group) and 15 healthy controls without TCC experience during walking and crossing obstacles of three different heights. Crossing angles of the pelvis and lower limbs and toe-obstacle clearances were obtained and analyzed using two-way analyses of variance to study the between-subject (group) and within-subject (height) effects. A multi-link system approach was used to reveal the relationship between joint angular changes and toe-obstacle clearances. Results Compared to the controls, the TCC group showed increased leading and trailing toe-obstacle clearances (p < 0.05) with increased pelvic hiking and hip flexion but decreased hip adduction on the swing side and decreased knee flexion on the stance side during leading-limb crossing (p < 0.05), and increased pelvic hiking and anterior tilt but decreased hip adduction on the swing side, and decreased knee flexion on the stance side during trailing limb crossing (p < 0.05). All significant joint angular changes contributed to the increases in the toe-obstacle clearances. Conclusion The current study identified the kinematic changes of the pelvis and the lower limb joints and revealed a specific synergistic multi-joint kinematic strategy to reduce tripping risks during obstacle-crossing in older long-term TCC practitioners as compared to non-TCC controls. The observed multi-joint kinematic strategies and the associated increases in toe-obstacle clearances appeared to be related to the training characteristics of TCC movements. Long-term TCC practice may be helpful for older people in reducing the risk of tripping and the subsequent loss of balance.